Efimov States From Triple α Resonances - Zhang, S.; Huang, M.; Zheng, H.; Zhang, G.; Kohley, Z.; Ma, Y. G.; Yennello, S. J.; Bonasera, A. (HNPS Advances in Nuclear Physics, 2019)
The Efimov trimers in excited 12C nuclei, which no observation exists yet, are discussed by means of analyzing the experimental data of 70(64)Zn(64Ni) +70(64)Zn(64Ni )reactions at beam energy of E/A=35 MeV/nucleon. In heavy ion collisions, the αs interact with each other and can form complex systems such as 8Be and 12C. For the 3α systems, multi resonance processes give rise to excited levels of 12C. The interaction between any two of the 3α particles provides events with one, two or three 8Be. Their interfering levels are clearly seen in the minimum relative energy distributions. Events of three couple αrelative energies consistent with the ground state of 8Be are observed with the decreasing of the instrumental error at the reconstructed 7.458 MeV excitation energy of 12C, which was suggested as the (Thomas) Efimov state.